Good grief : a companion for every loss - Westberg, Granger E. (Good Grief., 2019)
Timeless wisdom for all who grieve. Good Grief offers valuable insights on the emotional and physical responses persons may experience during the natural process of grieving. Reflection questions help readers explore their own experience with each stage. Whether mourning the death of a loved one, the end of a marriage, the loss of a job, or other difficult life changes